An epizootiological survey of sheep pox in Greece from 1982 to 1998 - MANGANA-VOUGIOUKA (Ο. ΜΑΓΤΑΝΑ-ΒΟΥΠΟΥΚΑ) O.; NOMIKOU (Κ. ΝΟΜΙΚΟΥ) K.; PANAGIOTATOS (Δ. ΠΑΝΑΠΩΤΑΤΟΣ) D.; BAKANDRITSOS (Ν. ΜΠΑΚΑΝΔΡΙΤΣΟΣ) N.; KOPTOPOULOS (Γ. ΚΟΠΤΟΠΟΥΛΟΣ) G. (Journal of the Hellenic Veterinary Medical Society, 2018)
Sheep pox outbreaks in Greece during the last 17 years are reviewed. It is believed that the disease is mostly introduced from eastern neighboring countries. The transmission of the virus is connected to the movements and contact of sheep flocks. It is also attributed to human-animal contacts. Disease foci appeared in several central and northeastern areas of the country. Between 1982 and 1986 the country remained sheeppox free. The first outbreak appeared in the island of Lesbos in 1987. In 1988 sheeppox outbreaks did occur in the Evros prefecture. In 1994 one new outbreak occurred in Evros. During the 1995-1998 period several outbreaks occurred in Evros and other regions, such as in Thessaloniki (1995), Larissa, Xanthi, Rodopi, Kavala, Magnissia, and Lemnos island (1996), Kavala, Magnissia, Halkidiki, and Samothraki island (1997). In 1998 the cases of sheeppox were reduced and occurred only in prefecture of Evros.